The Effect of Liquidity and Financial Distress on Tax Aggressiveness with Firm Size as The Moderating Variable - Maulida, Feriyana; Hasanah, Nuramalia; Sariwulan, Tuty (ITQAN: Journal of Islamic Economics, Management, and Finance, 2023)
Tax aggressiveness is an act of tax planning to minimize the tax expense both legally (tax avoidance) and illegally (tax evasion). This study aims to analyze the effect of liquidity and financial distress on tax aggressiveness with firm size as the moderating variable. The analysis used multiple linear regression (MLR) and moderate regression analysis (MRA). The population in this study is represented by state-owned enterprises (BUMN) and companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The sampling technique of this study was using a purposive sampling technique. The results show that liquidity negatively and significantly affected tax aggressiveness. Financial distress had a positive and significant effect on tax aggressiveness. Firm size did not affect tax aggressiveness. Firm size can moderate the effect of liquidity on tax aggressiveness, and firm size cannot moderate the effect of financial distress on tax aggressiveness.